2018
DOI: 10.1111/ejh.13132
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of thrombopoietin receptor agonists for persistent clinically relevant thrombocytopenia after allogeneic stem cell transplantation

Abstract: This study adds further enthusiasm for continued research on the use of these agents for the treatment of persistent thrombocytopenia in alloSCT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 19 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…Most of the studies included in this review were not powered to detect these differences. compared to older patients and a trend toward better response in patients who previously responded to filgrastim, 55 however, these trends were not seen in a larger study. 56 One study found that the use of anti-lymphocyte agents (or alemtuzumab) as part of the conditioning regimen was more common in the nonresponders than in the responders.…”
Section: Eltrombopag For Delayed Thrombocytopenia Following Hctmentioning
confidence: 65%
See 3 more Smart Citations
“…Most of the studies included in this review were not powered to detect these differences. compared to older patients and a trend toward better response in patients who previously responded to filgrastim, 55 however, these trends were not seen in a larger study. 56 One study found that the use of anti-lymphocyte agents (or alemtuzumab) as part of the conditioning regimen was more common in the nonresponders than in the responders.…”
Section: Eltrombopag For Delayed Thrombocytopenia Following Hctmentioning
confidence: 65%
“…[38][39][40][46][47][48][49][50][51][52][53][54] An additional 70 patients treated with romiplostim were reported in three articles that also included patients treated with eltrombopag as shown in Table 4. [55][56][57] Of the romiplostim treated patients, four reports included pediatric patients. 38,47,51,52 The median age was 50.…”
Section: Romiplostim For Delayed Thrombocytopenia Following Hctmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first approved for treatment of immune thrombocytopenia lasting for more than 6 months in adults 6 While the use of TPO-RA was retrospectively investigated in adult patients over the last few years, data regarding the potential benefit of these agents for pediatric posttransplant thrombocytopenia are lacking. [10][11][12][13] We report nine pediatric patients who received off-label ELT for thrombocytopenia occurring after allogeneic HSCT at three centers affiliated to the Italian Association of Pediatric Oncology and Hematology (AIEOP).…”
Section: Eltrombopag (Elt) Is An Oral Thrombopoietin Receptor (Tpo-r)mentioning
confidence: 99%